PENGARUH ALAT TIMBANG TERHADAP PEMAHAMAN KONSEP LAMBANG BILANGAN - Andryani, Fitri; Rosidah, Laily; Maryani, Kristiana (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2021)
This study aims to determine whether there is a significant effect of the use of weighing instruments on understanding the symbol of numbers in children aged 4-5 years in Sabilul Huda Cibungbulang PAUD Bogor. The type of research used is Quasi Experiment used in this study is Nonequivalent Control Group Design. The sample used is 4-5 years old which is divided into two classes / groups, namely class A1 as the experimental group and class A2 as the control class with a sample of 28 children. The data analysis technique used the help of Microsoft Excel computer program and SPSS version 24. From the independent sample test, the Sig (2-tailed) value of 0,000 was smaller than (0,05). There was a significant effect in the experimental class on the pre-test. the test obtained an average score of 5.00 before using the weighing instrument, after being given a weighing instrument obtained an average post-test score of 8.79, while in the control class the pre-test obtained an average score of 4.50 and for the post -test of 4.29, this shows that understanding the concept of number symbols of children aged 4-5 years who receive learning with weighing instruments is better than understanding the concept of number symbols of children aged 4-5 years who obtain conventional learning.Because the value of Sig (2-tailed) <α or thitung> ttable then HI is accepted and Ho is rejected. This means that there is a significant influence in the weighing tool on understanding the concept of number symbols in children aged 4-5 years in Sabilul Huda ECD.